2018
DOI: 10.1186/s40104-018-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Fat deposition deficiency is critical for the high mortality of pre-weanling newborn piglets

Abstract: BackgroundThe high mortality of pre-weanling piglets is a dominant challenge which severely restricts the development of pig industry. A number of factors including nutrients imbalance and temperature variation during postnatal period of piglets have been reported to closely associated with the high mortality of postnatal piglets. This study aims to find out the relationship between fat deposition and survival of newborn piglets.ResultsThere were no differences in organ coefficient and bone density between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…As shown in Figures 5(a) and 5(b), we found that BMS had no effect on the body bends of C. elegans, but it improved the frequency of head thrashes in glucose-treated worms, which inferred that BMS might slightly enhance the energy expenditure to lower the overall fat. Longevity of C. elegans is closely related with many factors, including environmental, dietary, and genetic factors [23,24]. High concentration of glucose is shown to exhibit a negative impact on the lifespan of nematodes [25].…”
Section: Influences Of Bms On the Locomotive Activity Progenymentioning
confidence: 99%
“…As shown in Figures 5(a) and 5(b), we found that BMS had no effect on the body bends of C. elegans, but it improved the frequency of head thrashes in glucose-treated worms, which inferred that BMS might slightly enhance the energy expenditure to lower the overall fat. Longevity of C. elegans is closely related with many factors, including environmental, dietary, and genetic factors [23,24]. High concentration of glucose is shown to exhibit a negative impact on the lifespan of nematodes [25].…”
Section: Influences Of Bms On the Locomotive Activity Progenymentioning
confidence: 99%
“…In recent years, growing evidences suggest that gut microbes are implicated in regulating macronutrient metabolism and absorption 40–45 . In the case of fat, Martinez‐Guryn et al 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Fats and oils are very essential raw materials possessing functional properties in many food products, such as butter, shortenings, and margarines 24–26 . Consumers select full or less fat products using their sight, and then sensed by mechanoreceptors in the mouth 27 .…”
Section: Role Of Fat In Food Productmentioning
confidence: 99%